Microbiological And Physicochemical Assessments of Selected Fish Pond Water Sample in South-West, Nigeria - Onajobi, Ismail Babatunde; Samson, Oyindamola John; Aina, Sulaimon Adebisi; Ogunmoye, Abdulrazaq Omotunde; Oyetade, Emmanuel Oladayo (Al-Hayat: Journal of Biology and Applied Biology, 2023)
Pathogenic organisms have the ability to reduce or delay fish output. The physicochemical characteristics and microbial population of fish pond water, play great roles in affecting the growth and development of fish. This study aims to assess the microbiological quality and physicochemical quality of fish pond water in Ijebu-North local government of Ogun state, Nigeria. Fish pond water samples were collected from three different locations, which include Ago-Iwoye, Ijebu-igbo and Awa. Physicochemical analysis of fish pond water samples were achieved by standard procedures and all parameters were subjected to World Health Organization standards (WHO). The microbiological examination was determined by different selective agar media and biochemical identification was achieved by conventional analysis. The physicochemical characteristics of the samples such as temperature, pH and conductivity ranged from 33.9-44.20C, 6.70-7.87 and 163-196 respectively. The presence of trace and toxic heavy metals such as calcium, zinc, copper, iron, lead and so on were detected in this study. The sample from Ijebu-Igbo had the highest bacteria count of 4.28x102 cfu/ml. Esherichia coli, Pseudomonas aeruginosa and Bacillus species have the highest occurrence among the isolates identified. Therefore, there is need for adequate treatment of fish pond water to reduce the risk of fish exposure to pathogens and heavy metals. This is to ensure that environmental parameters of water are in the optimum range that will enhance healthy fish production.